Tea consumption and risk of all-cause, cardiovascular disease, and cancer mortality: a meta-analysis of thirty-eight prospective cohort data sets - Youngyo Kim; Youjin Je (Epidemiology and Health)
OBJECTIVES Tea consumption has been considered beneficial to human health because tea contains phytochemicals such as polyphenols and theaflavins. We conducted a systematic review and meta-analysis on the association between tea consumption and mortality from all causes, cardiovascular disease (CVD), and cancer to provide a quantitative assessment of current evidence. METHODS The PubMed, Web of Science, and Scopus databases were searched through April 2024 to identify eligible studies. Random effects models were used to combine study-specific effect estimates (ESs). RESULTS A total of 38 prospective cohort data sets (from 27 papers) with 1,956,549 participants were included in this meta-analysis. The pooled ESs of the highest versus lowest categories of tea consumption were 0.90 (95% confidence interval [CI], 0.86 to 0.95) for all-cause mortality, 0.86 (95% CI, 0.79 to 0.94) for CVD mortality, and 0.90 (95% CI, 0.78 to 1.03) for cancer mortality. In the dose-response analysis, a non-linear association was observed. The greatest risk reductions were observed for the consumption of 2.0 cup/day for all-cause mortality (ES, 0.91; 95% CI, 0.88 to 0.94) and 1.5 cup/day for cancer mortality (ES, 0.92; 95% CI, 0.89 to 0.96), whereas additional consumption did not show a further reduction in the risk of death. A plateau was observed for CVD mortality at moderate consumption levels (1.5-3.0 cup/day), but a sustained reduction in mortality risk was observed at higher intake levels. CONCLUSIONS Moderate tea consumption (e.g., 1.5-2.0 cup/day) was associated with lower all-cause, CVD, and cancer mortality compared to no tea consumption. Further well-designed prospective studies are needed for a definitive conclusion.